The Relationship Between Body Composition and 12-Minute Run Test Among Cadet Medical Students in the Undergraduate Medical Program, Republic of Indonesia Defense University - Disty Chania; Justin Munawar; Hanum Fadhilah; Antonius Reuben; Grace Corlesa; Roby Firmansyah; Markus Wibowo; Nirawan Putranto (Perkumpulan Kedokteran Militer, 2025)
Background: Body composition influences physical performance, including running ability. Muscle mass and fat mass are important determinants of strength, endurance, and movement efficiency. This study analyzed the relationship between body composition and 12-minute running distance among cadet medical students. Methods: This quantitative observational analytic study used a cross-sectional design. Cadet medical students from Cohort 4 of the Republic of Indonesia Defense University were recruited. Body composition was measured using bioelectrical impedance analysis, and running performance was assessed with a 12-minute run test. Associations between muscle mass, fat mass, and running distance were analyzed using simple linear regression. Results: Seventy-two cadets were included. The mean muscle mass was 43.5%, mean fat mass was 21.6%, and mean 12-minute running distance was 2376 m. Muscle mass showed a strong positive correlation with running distance, whereas fat mass showed a strong negative correlation. Male cadets had higher muscle mass and achieved longer running distances than female cadets. Conclusion: Body composition is significantly associated with 12-minute running performance. Higher muscle mass supports better running distance, whereas higher fat mass reduces running efficiency. Individualized training and nutritional strategies should consider body composition to optimize cadet fitness.